Incidental fishing of Epinephelus itajara (Lichtenstein, 1822): the vulnerability of a critically endangered species of the Brazilian coast (Research, Society and Development, 2022)
Epinephelus itajara, popularly known as grouper, has a wide distribution and is considered the largest fish in the Atlantic Ocean. Behavioral characteristics allied to overfishing and degradation of marine habitats caused declines in E. itajara populations throughout the entire geographic distribution area. The goliath grouper is currently ranked on the IUCN RedList as Vulnerable in Global Status and Critically Endangered in the Gulf of Mexico. In Brazil, even with a fishing moratorium that has protected it since 2002, the species is categorized as critically endangered in the Red Book of the Instituto Chico Mendes de Conservação da Biodiversidade. Taking into account these factors and the information gap on the goliath grouper, this study addresses an account of an occasional “post mortem” encounter with a specimen on the edge of Pajuçara beach, Maceió - Alagoas. It was an adult individual, whose size was estimated at 1.6 m and 70 kg of body mass. This study also presents discussions about the conservation status of the species and the efficiency in the management of marine protected areas, revealing that even with many marine protection areas, incidental captures and port records are still recurrent on the Brazilian coast. This record highlights the need to reinforce inspections, in addition to suggesting that the management of these areas be more efficient, ensuring the reestablishment of grouper populations in the region.